Pembagian Masker di Alun-Alun Kota Klaten sebagai Upaya Pencegahan Peningkatan Covid-19 - Makhabbah Jamilatun (Universitas Muhammadiyah Mataram, 2022)
Abstract: The discipline of wearing a mask can reduce viral infections that spread through the respiratory tract. Residents around Klaten Town Square have a variety of activities. Some of them were still found not wearing masks. Therefore, in this community service, community service activities are carried out with the aim that residents who are visiting and doing activities around Klaten City Square increase the application of health protocols to prevent Covid-19 with discipline in using masks. This service activity is carried out through several stages. First, a survey of the target group was conducted. Second, identify the need for service activities. Third, the preparation of facilities and infrastructure needed in service activities. Fourth, is the implementation of service activities. In the implementation of community service activities, masks are given to residents who are and have activities around the Square, including residents who want to go to the Grand Mosque that crosses the Square, residents who visit around the Square, owners of transportation facilities, and traders in the area. around the Klaten Town Square. The response of residents who are visiting and active in Klaten City Square to this activity is good and very supportive. Residents around the square helped especially with the availability of masks. Community service activities went smoothly and the purpose of the activity was achieved, namely residents who were visiting and doing activities around Klaten City Square were disciplined in using masks.Abstrak: Disiplin penggunaan masker dapat mengurangi infeksi virus yang menyebar melalui saluran pernapasan. Warga di sekitar Alun-Alun Kota Klaten memiliki beragam aktivitas. Beberapa dari mereka masih ditemukan tidak memakai masker. Maka dari itu, dalam pengabdian masyarakat ini dilakukan kegiatan pengabdian kepada masyarakat dengan tujuan agar warga yang sedang berkunjung dan beraktivitas di sekitar alun-Alun Kota Klaten meningkatkan penerapan protokol kesehatan terhadap pencegahan covid-19 dengan disiplin dalam menggunakan masker. Kegiatan pengabdian ini dilakukan melalui beberapa tahapan. Pertama, dilakukan survei kelompok sasaran. Kedua, identifikasi kebutuhan kegiatan pengabdian. Ketiga, persiapan sarana dan prasarana yang diperlukan dalam kegiatan pengabdian. Keempat, pelaksanaan kegiatan pengabdian. Pada pelaksanaan kegiatan pengabdian masyarakat, masker diberikan kepada warga yang berada dan beraktivitas di sekitar Alun-Alun, diantaranya adalah warga yang hendak ke Masjid Raya yang melintasi Alun-Alun, warga yang berkunjung di sekitar Alun-Alun, pemilik sarana transportasi serta para pedagang di sekitar Alun-Alun Kota Klaten. Tanggapan warga yang sedang berkunjung dan beraktivitas di Alun-Alun Kota Klaten terhadap kegiatan ini adalah baik dan sangat mendukung. Warga di sekitar Alun-Alun, terbantu terutama dalam ketersediaan masker. Kegiatan pengabdian kepada masyarakat berjalan dengan lancar dan tercapai tujuan kegiatan yaitu warga yang sedang berkunjung dan beraktivitas di sekitar alun-Alun Kota Klaten disiplin dalam menggunakan masker.